Prescription for nutritional healing - Balch, Phyllis A (New York Avery, 2006)
Natural health's number-one bestseller for more than twenty years, completely revised and updated. With more than five million copies sold, Prescription for Nutritional Healing is the most trusted, comprehensive source on dietary supplements, vitamins, minerals, and herbs. A pioneer in the field of nutritional healing, Phyllis Balch passionately and meticulously researched and compiled this groundbreaking book. Now, a generation later, her message has more relevance than ever: consume fresh foods, avoid processed foods and those high in saturated fat, and optimize your intake of essential nutrients with the right supplements. Today's well-stocked vitamin and natural-health stores can be confusing, and people need Balch's clear, concise, landmark guide. To help them make sense of the mind-numbing array of choices that are available, readers of Prescription for Nutritional Healing will: - learn the basics of good nutrition; - find out how to balance vitamins and minerals so that the body can properly absorb both; - determine how best to treat 250 problems-from abscesses to wrinkles-using herbs, nutrition, and supplements; and - get the facts on other complementary therapies, like ayurveda, biofeedback, chiropractic care, and more. Prescription for Nutritional Healing is an essential resource for every health-minded consumer.
CONTENTS Preface, xiii How to Use This Book, xv Part One Understanding the Elements of Health Introduction, 3 Nutrition, Diet, and Wellness, 5 Vitamins, 15 Minerals, 30 Air, 41 Water, 44 Amino Acids, 51 Antioxidants, 62 Enzymes, 69 Natural Food Supplements, 73 Herbs, 96 Drug Interactions, 130 Part Two The Disorders Introduction, 000 Troubleshooting for Disorders, 000 Common Disorders, 000 Abscess, 000 Acid/Alkali Imbalance, 000 Acne, 000 Adrenal Disorders, 000 Age Spots, 000 Aging, 000 AIDS, 000 Alcoholism, 000 Allergies, 000 Aluminum Toxicity, 000 Alzheimer's Disease, 000 Anemia, 000 Anorexia Nervosa, 000 Anxiety Disorder, 000 Appendicitis, 000 Appetite, Poor, 000 Arsenic Poisoning, 000 Arteriosclerosis/Atherosclerosis, 000 Arthritis, 000 Asthma, 000 Athlete's Foot, 200 Attention Deficit Disorder (ADD)/ Attention Deficit Hyperactivity Disorder (ADHD), 000 Autism, 000 Backache, 000 Bedsores, 000 Bed-Wetting, 000 Bee Sting, 000 Bladder Infection (Cystitis), 000 Boil, 000 Breast Cancer, 000 Breastfeeding-Related Problems, 000 Engorgement, 000 Mastitis (Breast Infection), 000 Plugged Duct, 000 Sore Nipples, 000 Bronchitis, 000 Bruising, 000 Bruxism, 000 Bulimia, 000 Burns, 000 Bursitis, 000 Cadmium Toxicity, 000 Cancer, 000 Candidiasis, 000 Canker Sores (Aphthous Ulcers), 000 Cardiovascular Disease, 000 Carpal Tunnel Syndrome, 000 Celiac Disease, 000 Chemical Allergies, 000 Chemical Poisoning, 000 Chickenpox, 000 Chlamydia, 000 Chronic Fatigue Syndrome, 000 Circulatory Problems, 000 Cirrhosis of the Liver, 000 Cold Sores (Fever Blisters), 000 Common Cold, 000 Constipation, 000 Copper Deficiency, 000 Copper Toxicity, 000 Corns and Calluses, 000 Crohn's Disease, 000 Croup, 000 Cystic Fibrosis, 000 Dandruff, 000 Depression, 000 Dermatitis, 000 Diabetes, 000 Diarrhea, 000 Diverticulitis, 000 Dog Bite, 000 Down Syndrome, 000 Drug Addiction (Substance Abuse), 000 Dry Skin, 000 Ear Infection, 000 Edema, 000 Emphysema, 000 Endometriosis, 000 Environmental Toxicity, 000 Epilepsy, 000 Eye Problems, 000 Bags under the Eyes, 000 Bitot's Spots, 000 Blepharitis, 000 Bloodshot Eyes, 000 Blurred Vision, 000 Cataracts, 000 Colorblindness, 000 Conjunctivitis (Pinkeye), 000 Corneal Ulcer, 000 Diabetic Retinopathy, 000 Dimness or Loss of Vision, 000 Dry Eyes, 000 Eyestrain, 000 Floaters, 000 Glaucoma, 000 Itchy or Tired Eyes, 000 Macular Degeneration, 000 Mucus in the Eyes, 000 Photophobia, 000 Retinitis Pigmentosa, 000 Scotoma, 000 Shingles (Herpes Zoster), 000 Stye, 000 Thinning Eyelashes, 000 Ulcerated Eyelid, 000 Xerophthalmia, 000 Fever, 000 Fibrocystic Breasts, 000 Fibroids, Uterine, 000 Fibromyalgia Syndrome, 000 Foodborne/Waterborne Disease, 000 Fracture, 000 Frigidity, 000 Fungal Infection, 000 Gallbladder Disorders, 000 Gangrene, 000 German Measles (Rubella), 000 Glaucoma, 000 Gout, 000 Growth Problems, 000 Hair Loss, 000 Halitosis (Bad Breath), 000 Hay Fever, 000 Headache, 000 Hearing Loss, 000 Heart Attack, 000 Heartburn/Gastroesophageal Reflux Disease (GERD), 000 Heel or Bone Spur, 000 Hemophilia, 000 Hemorrhoids, 000 Hepatitis, 000 Herpesvirus Infection, 000 High Blood Pressure (Hypertension), 000 High Cholesterol, 000 Hives, 000 Hyperthyroidism, 000 Hypoglycemia (Low Blood Sugar), 000 Hypothyroidism, 000 Hysterectomy-Related Problems, 000 Impotence, 000 Incontinence, 000 Indigestion (Dyspepsia), 000 Infertility, 000 Inflammation, 000 Influenza, 000 Insect Allergy, 000 Insect Bite, 000 Insomnia, 000 Irritable Bowel Syndrome, 000 Jaundice, 000 Kidney Disease (Renal Failure), 000 Kidney Stones, 000 Lactose Intolerance (Lactase Deficiency), 000 Lead Poisoning, 000 Leg Ulcers, 000 Legionnaires' Disease, 000 Lupus, 000 Lyme Disease, 000 Malabsorption Syndrome, 000 Manic-Depressive Disorder (Bipolar Mood Disorder), 000 Measles, 000 Memory Problems, 000 M?ni?re's Disease, 000 Meningitis, 000 Menopausal and Perimenopausal Problems, 000 Mercury Toxicity, 000 Migraine, 000 Mononucleosis, 000 Motion Sickness, 000 Multiple Sclerosis, 000 Mumps, 000 Muscle Cramps, 000 Nail Problems, 000 Narcolepsy, 000 Nickel Toxicity, 000 Nosebleed, 000 Obesity, 000 Oily Skin, 000 Osteoporosis, 000 Paget's Disease of Bone, 000 Pancreatitis, 000 Parkinson's Disease, 000 Peptic Ulcer, 000 Periodontal Disease, 000 Pneumonia, 000 Poison Ivy/Poison Oak/Poison Sumac, 000 Poisoning, 000 Polyps, 000 Pregnancy-Related Problems, 000 Anemia, 000 Asthma, 000 Backache, 000 Bladder Discomfort/Infection, 000 Bleeding Gums, 000 Constipation, 000 Coughs and Colds, 000 Depression, 000 Diabetes, Gestational, 000 Dizziness, 000 Eclampsia and Preeclampsia, 000 Ectopic Pregnancy, 000 Edema (Swelling of the Hands and Feet), 000 Gas (Flatulence), 000 Groin Spasm, Stitch, or Pressure, 000 Heartburn, 000 Hemorrhoids, 000 Insomnia, 000 Leg Cramps, 000 Miscarriage (Spontaneous Abortion), 000 Morning Sickness, 000 Nosebleeds and Nasal Congestion, 000 Sciatica, 000 Skin Problems, 000 Soreness in the Rib Area, 000 Stretch Marks, 000 Sweating, 000 Varicose Veins, 000 Premenstr
Includes bibliographical references and index
Keywords: Nutrition - Popular works; Dietary supplements - Popular works; Herbs - Therapeutic use - Popular works